Reflection on Researching Teachers' Professional Integrity: Being in the Setting of Ethnography - Munakarmi, Rupa (Journal of Education and Research, 2016)
This short article is a reflective product of my experiences and learning while engaging in six month long ethnographic fieldwork with teachers from semi urban and rural community schools in Kavre district, Nepal. As an ethnographic researcher, I am still in contact with my research participants in doing peer review and reflection of the listening, seeing and being within the topic. Specifically, this note reflects my positionality and challenges of interviewing, observing and presenting the initial findings. Moreover, this reflective note highlights ethnography as both a process and a product that evolves during the study time itself.